Numerical Modeling of Damage Evolution Phenomenon in Solid-State Lithium-Ion Batteries. Issue 12 (1st January 2017) - Behrou, Reza; Maute, Kurt
Abstract : This paper presents a finite element methodology for numerical modeling the evolution of damage in Solid-State Lithium-Ion Batteries (SSLIBs). This process is dominated by the interaction of electrochemical and mechanical phenomena in the electrode, solid-state electrolyte, and electrode/electrolyte interface. These phenomena depend on the transport process of species/ions, mechanical deformations, electrostatics, and electrochemical reactions. Damage evolution in the electrode active material, caused by diffusion-induced stresses, is described by a non-local damage model. To model the influence of the damage evolution on the ion/species transport and the electrochemical performance of the battery, the diffusivity of the electrode is coupled with the damage evolution. The impact of damage evolution on the electrochemical and mechanical responses of the SSLIB is studied by numerical examples. The results indicate that the evolution of the damage during a cyclic charge/discharge process diminishes the electrochemical and mechanical performances of the battery by reducing the transport properties, decreasing the capacity, and lessening the strength of the active material. The numerical studies further suggest that electrode particles with large aspect ratios have better performance and decrease the damage-induced capacity fade.